Pengaruh Disiplin Kerja terhadap Kinerja Karyawan Cipta Hotel Pancoran Jakarta Selatan - Eigis Yani Pramularso (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
Abstract  –  One of the things that the company's priority to achieve the goal is to have professional resources with the best employee performance in carrying out its work. One that can be affect employee’s performance is the existence of work discipline. This work discipline should be continue to be held and become the principle for employees, so that employee’s contribution in supporting the success of various functions of the company's operations become more optimal. The aims of this study is to determine the effect of work discipline on employee’s performance Cipta Hotel Pancoran South Jakarta. The number of respondents in this study is 50 employee’s. The data were collected by using questionnaires and library studies. Data analysis is used the linearity test, simple regression analysis, and correlation coefficient test. The result shows that the discipline of work has a positive and significant impact on the performance of employee’s of Cipta Hotel Pancoran, South Jakarta. The magnitude of the correlation coefficient shows the amount of 0.499, it means the relationship of work discipline to the employee's performance is quite strong. Coefficient of determination or R Squared = 0.249 it means that work discipline affect of employee’s performance is 24.9% while the rest is influenced by factors others than work discipline it self. Key Word: work discipline, employee performance